Stress and burnout in health professionals - Gonçalves, Maria Alice Oliveira (2019)
Occupational stress and burnout are a global epidemic that can cause severe nega-tive effects on workers’ physical and emotional health. Health professionals working in a hospital setting are especially at risk, due to the inherent characteris-tics of their work. Consequently, this study aimed to analyse the relationships be-tween stress and burnout in health professionals working in a hospital in the North of Portugal. A convenience sample of 221 health professionals participated in this cross-sectional study and answered two instruments to assess stress and burnout at work. Results showed that stress dimensions, such as the precarious-ness of the contractual status, the intention to change services, work overload, stress from the work-home interface, relationships at work, leading training activ-ities, and dealing with patients predicted the three dimensions of burnout – physi-cal fatigue, cognitive weariness, and emotional exhaustion. Therefore, these find-ings contribute to increase the knowledge of health professional’s mental condi-tions, and can be used to design and implement interventions to mitigate the ef-fects of stress and burnout on these professionals.